Spatial-Based Information System for Early Precaution of Dengue Hemorrhagic Fever - Yulianti, N.; Raharjo, Mursid; Sediyono, Eko (International Journal of English Literature and Social Sciences (IJELS), 2019)
Dengue hemorrhagic fever (DHF) case in Tegal is quite high. In recent years (2016-2018), there has been an outbreak of dengue hemorrhagic fever which resulted in 24 deaths. In this regard, a fast and accurate control system is needed. One of them is spatial-based interactive information system for DHF. This study aimed to develop a spatial-based DHF information system that produced complete, accurate, easily accessible, and punctual information. DHF information system developed was website-based. This research was a research survey with qualitative approach. Qualitative data were collected by observation and interview methods. Sampling based on purposive sampling method. System development using the FAST method. Pre and Post data collection time approaches by assessing respondents' perceptions of the quality of information produced by the system before and after the development of the information system. The result of this study was a spatial-based interactive DHF information system with output map of the location of DHF cases according to the patient’s address and DHF risk factors in the form of ABJ and altitude. Testing the quality of information before and after the development of the DHF information system, showed a weighted average increase in five aspects of information quality.